Curcumol inhibits the expression of programmed cell death-ligand 1 through crosstalk between hypoxia-inducible factor-1α and STAT3 (T705) signaling pathways in hepatic cancer. (15th July 2020) - Zuo, Hong Xiang; Jin, Yong; Wang, Zhe; Li, Ming Yue; Zhang, Zhi Hong; Wang, Jing Ying; Xing, Yue; Ri, Myong Hak; Jin, Cheng Hua; Xu, Guang Hua; Piao, Lian Xun; Ma, Juan; et al.
Abstract: Ethnopharmacological relevance: Curcuma wenyujin is a Chinese traditional herbal medicine that is commonly used as an anti-oxidant, anti-proliferative, and anti-tumorigenic agent. Curcumol is a representative index component for the quality control of the essential oil of Curcuma wenyujin, which is currently used as an anti-cancer drug, and is included in the State Pharmacopoeia Commission of the People's Republic of China (2005). However, the mechanisms of action and molecular functions of curcumol are not yet fully elucidated. Aim of the study: This study aimed to identify new effects of curcumol from the perspective of cancer immunotherapy. Materials and methods: The underlying mechanism of the inhibition of programmed cell death-ligand 1 (PD-L1) activation by curcumol was investigated in vitro via homology modeling, molecular docking experiments, luciferase reporter assays, MTT assays, RT-PCR, western blotting, and immunofluorescence assays. Changes in cellular proliferation, angiogenesis, and the tumor-killing activity of T-cells were analyzed via EdU labeling, colony formation, flow cytometry, wound-healing, Matrigel Transwell invasion, tube formation, and T-cell killing. The anti-tumor activity of curcumol was assessed i n vivo in a murine xenograft model using Hep3B cells. Results: Curcumol reduced the expression of phosphorylated signal transducer and activator of transcription 3 (p-STAT3) via JAK1, JAK2, and Src pathways and inhibited hypoxia-inducible factor-1α (HIF-1α) protein synthesis via mTOR/p70S6K/eIF4E and MAPK pathways. Furthermore, we revealed crosstalk between STAT3 and HIF-1α pathways, which collaboratively regulated PD-L1 activation, and that curcumol played a role in this regulation. Curcumol inhibited cell proliferation, S-phase progression, tube formation, invasion, and metastasis by inhibiting PD-L1. In addition, curcumol restored the activity of cytotoxic T-cells and their capacity for tumor cell killing by inhibiting PD-L1. In vivo experiments confirmed that curcumol inhibited tumor growth in a xenograft model. Conclusions: These results illustrated that curcumol inhibits the expression of PD-L1 through crosstalk between HIF-1α and p-STAT3 (T705) signaling pathways in hepatic cancer. Thus, curcumol might represent a promising lead compound for the development of new targeted anti-cancer therapeutics. Graphical abstract: Image 1 Highlights: Curcumol inhibits HIF-1α protein synthesis and STAT3 activation. Curcumol inhibits the expression of PD-L1 by crosstalk between STAT3 and HIF-1α. Curcumol inhibits cell proliferation and angiogenesis by suppressing PD-L1. Curcumol restores the tumor-killing activity of T-cells by inhibition of PD-L1. Curcumol inhibits the growth of Hep3B cells in a xenograft tumor model.